Monitoring readiness to train and perform in female football: Current evidence and recommendations for practitioners - Beato, M.; Madsen, E. E.; Clubb, J.; Emmonds, S.; Krustrup, P. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Monitoring player readiness to train and perform is an important practical concept in football. Despite an abundance of research in this area in the male game, to date, research is limited in female football. The aims of this study were, first, to summarize the current literature on the monitoring of readiness in female football; second, to summarize the current evidence regarding the monitoring of the menstrual cycle and its potential impact on physical preparation and performance in female footballers; and third, to offer practical recommendations based on the current evidence for practitioners working with female football players.